Efektivitas Kelas Ibu Hamil terhadap Kesiapan Persalinan Ibu Hamil Trimester II dan III di Puskesmas Bantul 2 Kabupaten Bantul - Rani Ayu Hapsari; Isti Chana Yuliati; Rahsunji Intan; Margiyati Margiyati; Khansa Nabila Putri; Sri Agita (Institut Nalanda, 2026)
One of the strategies to lower the Maternal Immortality Rate (AKI) and the Infant Immortality Rate (AKB) is to provide education for pregnant women is the knowledge of pregnant women whose purpose is to provide information to pregnant women about pregnancy problems and how to overcome them so that pregnant women are ready to face the problem. The mother's unpreparedness in dealing with coping can contribute to the high level of AKI. Keilas Pregnant Women is specially designed for pregnant women to provide education and support from the beginning of pregnancy to the beginning of pregnancy. The purpose of this research is to determine the effectiveness of the effectiveness of pregnant women in the face of the contents of the questionnaire in pregnant women in trimeisteir II and III at the Bantul 2 Puskeismas Bantul Regency. Meitodei peineilitian meingus, quasy eikspeirimein. The sample of this research is pregnant women in trimeisteir II and III who are registered in the registry of pregnant women at the Bantul 2 Health Center in Bantul Regency in July 2025 as many as 30 people. The technique of sampling is used to measure the total sampling. The results of the study showed that while pregnant women were in the same situation, a proportion of pregnant women were ready to face the test (66.67%), while 33.33% were ready. As long as all pregnant women follow the knowledge of pregnant women in an effective way, 100% of pregnant women say they are ready to face the copy. Statistical analysis showed a value of p = 0.000 (< 0.05), which indicates a significant increase in the content of pregnant women during and after following the pregnancy cycle. Deingan deimikian, the implementation of the efficacy of pregnant women is proven to increase the mother's content in dealing with the divorce.